Novel Trichoderma Isolates Alleviate Water Deficit Stress in Susceptible Tomato Genotypes - Rawal, Ranjana; Scheerens, Joseph C.; Fenstemaker, Sean M.; Francis, David M.; Miller, Sally A.; Benitez, Maria-Soledad (Frontiers in Plant Science, 2022)
Symbiotic fungi in the genus Trichoderma can induce abiotic stress tolerance in crops. The beneficial effects of Trichoderma on water deficit stress is poorly understood and may be isolate-specific. Our objective was to evaluate a collection of Nepalese Trichoderma isolates and their efficacy to improve tomato (Solanum lycopersicum) growth under water deficit. Variable growth in low moisture environments was observed among Trichoderma isolates from Nepal, Ohio, and commercial sources using in-vitro assays. Overall performance of the population decreased when cultured under conditions of decreasing matric water potential (0.0, -2.8, -4.8, and -8.5 Ψ). Twelve isolates were selected for evaluation for their potential to elicit drought tolerance in greenhouse-grown ‘Roma Organic’ tomatoes.  Plants treated with T. asperelloides-NT33 had higher shoot weight than the non-inoculated control (T0) under water deficit stress conditions. Further, the stress-reducing efficacy of isolates T. asperelloides-NT33, T. asperellum-NT16, T. asperelloides-NT3, and commercial T. harzianum-T22 were tested on tomato genotypes with differing tolerance to drought [‘Roma Organic’, ‘Jaune Flamme’, and ‘Punta Banda’]. The water deficit susceptible genotypes ‘Roma Organic’ and ‘Jaune Flamme’ inoculated with isolate NT33 had significantly higher shoot weight (37% and 30% respectively; p<0.05) compared to the non-inoculated control under water deficit stress conditions. In drought tolerant ‘Punta Banda’, shoot weight was also significantly greater in NT33 inoculated plants under water deficit stress conditions, but with lower magnitude difference (8%; p <0.05).  Our results demonstrate differences in the ability of Trichoderma isolates to confer tolerance to water deficit in tomato with NT33 potentially relieving stress. Tomato genotypes also play a role in the outcome of interactions with the Trichoderma isolates we tested.